2021
DOI: 10.1515/ijamh-2021-0116
|View full text |Cite
|
Sign up to set email alerts
|

Significance of sugar intake in young adults: a review

Abstract: Background Foodborne diseases non-communicable diseases (NCDs) are the main reason of death, accounting for 38 million (68%) of the 56 million premature deaths worldwide in 2012. Lower-middle and middle-income countries accounted for nearly three-quarters of all NCD fatalities (28 million), as well as the bulk of illness and premature death (82%). An excessive consumption of added sugar is source of worry for its link to unhealthy nutrition quality, overweight, and the risk of NCDs among adol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…Diets rich in such products are now well-known to increase the risk for chronic diseases associated with metabolic imbalances, including obesity [ 38 , 41 , 42 ]), type II diabetes [ 42 ], and cardiovascular diseases [ 43 ], amongst other chronic pathological alterations, indicating that HS diets cause important metabolic changes, which can result in MS. This is particularly important considering the early age intake of HS [ 1 , 2 , 3 , 4 , 5 ]. Indeed, a recent analysis of the global scenario demonstrated that nearly 3% of children and 5% of the adolescent population present with MS [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Diets rich in such products are now well-known to increase the risk for chronic diseases associated with metabolic imbalances, including obesity [ 38 , 41 , 42 ]), type II diabetes [ 42 ], and cardiovascular diseases [ 43 ], amongst other chronic pathological alterations, indicating that HS diets cause important metabolic changes, which can result in MS. This is particularly important considering the early age intake of HS [ 1 , 2 , 3 , 4 , 5 ]. Indeed, a recent analysis of the global scenario demonstrated that nearly 3% of children and 5% of the adolescent population present with MS [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…The intake of high-content sugar foods and beverages from an early age has been linked to an increased risk of obesity, type II diabetes, and cardiovascular diseases, amongst other chronic pathological alterations [ 1 , 2 , 3 , 4 , 5 ]. Sucrose is a disaccharide composed of 50% glucose and 50% fructose commonly added to foods and drinks as a sweetener [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Often neglected and underestimated, painful cavities have an important impact on overall health by altering eating, attention, sleep, mood and social relationships. Most importantly, if left untreated, dental caries can lead to death from sepsis [ 4 , 5 ]. Therefore, dental caries is a critical global health issue, especially in areas where dental care is not readily available, such as in circumpolar areas [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, the risk factor for caries depends greatly on the way of life. For example, in the populations of European ancestry, dental caries was moderately frequent for a few thousand years until the prevalence increased considerably after the industrial revolution and the abundant consumption of industrial sugars [ 5 , 12 ]. Very recently, the severity of dental caries has decreased in these populations due to considerable efforts in prevention [ 13–15 ].…”
Section: Introductionmentioning
confidence: 99%